Well Spent : How Governance Determines the Effectiveness of Infrastructure Investments - Kornejew, Martin; Rentschler, Jun; Hallegatte, Stephane (World Bank, Washington, DC, 2019)
This study explores the role of governance in improving infrastructure reliability. It estimates that increasing infrastructure spending and improving governance in parallel is six times more effective at enhancing transport system performance than increasing spending alone. It also estimates that under current fiscal budgeting, every $1 spent on infrastructure maintenance is as effective as $1.5 of new investments in many OECD economies. Overall, the evidence in this study demonstrates that it is the quality rather than the quantity of infrastructure spending that determines the quality of infrastructure services.